Hegemonía norteamericana en Medio Oriente. Algunas premisas - Aranda, Gilberto; Morandé, José (Revista de Estudios Árabes, 2014)
Before the nineties, the U.S.A., aiming to preserve the existent U.S.A favorable system of commerce and hegemony, adopted some military global strategic concepts that infringed the sovereignty of certain countries. Since the early nineties, reacting against supposed threats to its interests worldwide, the U.S.A adopted stringent political and security considerations to maintain its supremacy. George Bush Jr. reinforced the fight against terror abroad (specially Islamic) with the help of some allies, and imposed stringent security measures at home. This policy also included the change of regimes (Iraq and Afghanistan) with the pretext that they constitute a direct threat to the U.S.A., and the installation of governments controlled by their American sponsors.